Malume's bones - Mokhele, Sizakele (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2018)
My poetry is about real stories: poverty, love, politics, past pains and healing. I try to follow the example of Amiri Baraka who says his poetry is whatever he thinks he is, that he makes poetry with "what can be saved out the garbage of our lives" . My collection also preserves and embraces demotic language, which is also a part of who I am. I am influenced by Baraka's and Ike Muila's use of demotics, and the way that poets such as Antonio Jacinto, Costa Andrade and Mafika Gwala tackle political matters in a colourful and powerful way. I have also been inspired by ancient Chinese poets to explore love and eroticism, particularly how it plays out in the eyes of my people.
Keywords: Creative writing (Higher education) -- South Africa; South African poetry (English) -- 21st century